Successful Unrelated Stem Cell Transplantation in an Infant With Congenital Acute Myelogenous Leukemia FAB M5 Showing Massive Cutaneous Infiltrations—A Challenging Multidisciplinary Approach. Issue 1 (20th August 2015) - Lanz, Sofia; Schwinger, Wolfgang; Sovinz, Petra; Lackner, Herwig; Resch, Bernhard; Urlesberger, Berndt; Sipurzynski, Sabine; Urban, Christian
Abstract : The multidisciplinary management of a male neonate presenting with congenital acute myelogenous leukemia of monoblastic phenotype is reported using conventional chemotherapy, high dose conditioning, and matched unrelated donor stem cell transplantation. These therapies were combined to add a graft versus leukemia effect to the treatment. Although chimerism studies showed a decrease of donor white blood cells, T‐cells remained stable of allogeneic origin. We hypothesize that a continuous graft versus leukemia effect results in minimal residual disease negativity for now more than 18 months since stem cell transplantation. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.